PENINGKATAN MOTIVASI IBU RUMAH TANGGA UNTUK MEMANFAATKAN TANAMAN OBAT KELUARGA (TOGA) - Y. Kusumawaty; S. Khaswarina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
The tendency of society to return to nature have increased interest in herbal remedies. This conditionprovides business opportunities for variety of medicinal plants including the cultivation of family medicinalplants (TOGA). The purpose of this community service activity was to increase people's motivation toexploit the business opportunity of herbal plants collectively. The program was conducted in three steps: (1)approaching the problems faced by mothers in managing medicinal plants through interviews withcommunity leaders; (2) conducting training on the utilization of variety of crops into simple remedies and (3)evaluation of the training outcomes and motivation of training participants to develop the cultivation andprocessing of medicinal plants. The results showed that participants were motivated to develop medicinalplant business. Tips shared on how to manage medicinal plant gardens in groups were helpful to reduceindividual workload. In general, the implementation of training activities on the utilization of FamilyMedicinal Plants (TOGA) was quite successful. This can be seen from the participants’ request that thisactivity can continue to support them. Cultivation of medicinal plants is suitable as an alternative forhousewife empowerment because it can be done without leaving the important role as a mother.